Intellectual transformation of Ukraine's oil and gas industry for global competitiveness - Guz, O. B. (Східноєвропейський центр наукових досліджень, 2025)
The strategic transformation of Ukraine's oil and gas industry in the context of import dependence and growing global market competition is considered. In order to enter the international arena, it is necessary not only to extract resources, but also to intellectualise enterprise management. Despite external pressure, it is these challenges that are driving the revision of internal business processes. This study outlines key areas for implementing smart technologies and process optimisation to increase sustainability, efficiency and compliance with global energy standards.
Keywords: oil and gas industry; global market; enterprise management; business processes; intellectualisation of management